Resource management and performance of climate change adaptation projects in Kenya - Murungi, Violet; Huka, Guyo Sarr; Ntongai, David; Mworia, Eric (African Journal of Science, Technology and Social Sciences, 2025)
Climate change adaptation has emerged as a crucial area of concern due to Kenya’s susceptibility to climate change effects. Many climate change adaptation projects have been implemented across the country, both government and donor funded. This study examined the effects of resource management on the performance of climate change adaptation projects in Kenya. 11 climate change adaptation projects in Marsabit and Isiolo Counties, Kenya, with a total of 2,021 beneficiaries were targeted. A sample of 334 respondents was derived using Slovin’s Formula. Data collection tools included questionnaires for beneficiaries, interviews with key informants, and field observations. Data was analyzed using SPSS and Microsoft Excel. Descriptive statistics (mean and standard deviation) described the data, while inferential statistics (correlation and regression analysis) assessed relationships between variables. A strong positive correlation was found between resource management and project performance (correlation = 0.409, p=0.000). The regression analysis indicated a statistically significant effect (F = 50,355, p = 0.000) with a coefficient β = 0.393, suggesting that resource management positively influenced project success. The Adjusted R Squared attained was 0.168, which implied that resource management had a poor effect in explaining project performance. The study concludes that resource management is a critical factor for successful implementation and enhancing performance of climate change adaptation projects. It recommends that project implementers should identify, allocate and ensure adequacy of the necessary resources for implementation of projects. The study further recommends resource optimization for efficient utilization of available resources.